2-Aminothiazoles with Improved Pharmacotherapeutic Properties for Treatment of Prion Disease - Li, Zhe (2013)
Recently, we described the aminothiazole lead (4-biphenyl-4-yl-thiazol-2-yl)-(6-methyl-pyridin-2-yl)-amine (1), which exhibits many desirable properties, including excellent stability in liver microsomes, oral bioavailability of ∼40% and high exposure in the brains of mice. Despite its good pharmacokinetic properties, compound 1 exhibited only modest potency in mouse neuroblastoma cells overexpressing the disease-causing prion protein PrP(Sc). Accordingly, we sought to identify analogs of 1 with improved antiprion potency in ScN2a-cl3 cells while retaining comparable or superior properties. We now report the discovery of improved lead compounds such as (6-methyl-pyridin-2-yl)-[4-(4-pyridin-3-yl-phenyl)-thiazol-2-yl]-amine (15) and cyclopropanecarboxylic acid (4-biphenyl-thiazol-2-yl)-amide (34), which exhibited brain exposure/EC(50) ratios at least ten-fold greater than that of 1.